Impact of individual extracellular proteases on Staphylococcus aureus biofilm formation in diverse clinical isolates and their isogenic sarA mutants. Issue 6 (25th September 2014) - Loughran, Allister J.; Atwood, Danielle N.; Anthony, Allison C.; Harik, Nada S.; Spencer, Horace J.; Beenken, Karen E.; Smeltzer, Mark S.
Abstract We demonstrate that the purified Staphylococcus aureus extracellular proteases aureolysin, ScpA, SspA, and SspB limit biofilm formation, with aureolysin having the greatest impact. Using protease‐deficient derivatives of LAC, we confirmed that this is due to the individual proteases themselves. Purified aureolysin, and to a lesser extent ScpA and SspB, also promoted dispersal of an established biofilm. Mutation of the genes encoding these proteases also only partially restored biofilm formation in an FPR3757 sarA mutant and had little impact on restoring virulence in a murine bacteremia model. In contrast, eliminating the production of all of these proteases fully restored both biofilm formation and virulence in a sarA mutant generated in the closely related USA300 strain LAC. These results confirm an important role for multiple extracellular proteases in S. aureus pathogenesis and the importance of sarA in repressing their production. Moreover, purified aureolysin limited biofilm formation in 14 of 15 methicillin‐resistant isolates and 11 of 15 methicillin‐susceptible isolates, while dispersin B had little impact in UAMS‐1, LAC, or 29 of 30 contemporary isolates of S. aureus. This suggests that the role of sarA and its impact on protease production is important in diverse strains of S. aureus irrespective of their methicillin resistance status.